How it works : recovering citizens in post-welfare Philadelphia - Fairbanks, Robert P., II, 1968- (University of Chicago Press, 2009)
Of the some sixty thousand vacant properties in Philadelphia, half of them are abandoned row houses. Taken as a whole, these derelict homes symbolize the city's plight in the wake of industrial decline. But a closer look reveals a remarkable new phenomenon--street-level entrepreneurs repurposing hundreds of these empty houses as facilities for recovering addicts and alcoholics. How It Works is a compelling study of this recovery house movement and its place in the new urban order wrought by welfare reform. To find out what life is like in these recovery houses, Robert P. Fairbanks II goes insid.